If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + -11t = -9 Solving -20 + -11t = -9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -11t = -9 + 20 Combine like terms: -20 + 20 = 0 0 + -11t = -9 + 20 -11t = -9 + 20 Combine like terms: -9 + 20 = 11 -11t = 11 Divide each side by '-11'. t = -1 Simplifying t = -1
| 15-g=2g-23 | | -x+(-1.333+x)=3 | | 5-4(t+1)=t+6 | | 5x+76-8=2x-1 | | -2=4(k+8)-3k | | b=3-3/20*10 | | 120=(x+20)+4x | | 3-1/5e=7 | | x+6=8x | | 63+(-18)+12= | | x^2*x=1 | | 25j-163=12 | | 45x+75=255 | | -14=4n+3n | | 2+n=6 | | 1/x^2=x^2 | | 2x(2x+4)=2x+3 | | 9=4m-6-5 | | 4-5y=9-6y | | y=(7-2k)x | | 15-6=9 | | 7/12t-1/4=2y-5/3 | | Q-7=3 | | 4x+(x+20)=120 | | 19+(-19)= | | -10+4(3n+10)=18 | | 4y^2+19y+12= | | -6.5t+15=-9.7t-43.8 | | 3-7y=6-8y | | -64=-8(p+1) | | X(x-48)=180 | | 12+12n=-48 |